Performance evaluation of a SARS-CoV-2 and influenza A/B combo rapid antigen test - Rosenblatt, Kevin P.; Romeu, Hugo; Romeu, Camille; Granger, Elder (Frontiers in Molecular Biosciences, 2024)
Introduction: The global COVID-19 pandemic and seasonal influenza outbreaks have drawn attention to the critical need for accurate and efficient diagnostic tools. Methods: The performance of the InstaView COVID-19/Flu Ag Combo Test, which was designed to simultaneously detect the SARS-CoV-2, influenza A, and influenza B viruses, was analytically and clinically evaluated. Results: The InstaView COVID-19/Flu Ag Combo Test exhibited robust detection capabilities, accurately identifying SARS-CoV-2, influenza A, and influenza B viruses over a wide concentration range (1.41 × 103 to 7.05 × 104 TCID50/mL). Extensive testing against potential cross-reactants and interferences yielded no false-positive results, indicating the high specificity of the test. Clinical evaluation further confirmed the kit’s reliability, with sensitivity ranging from 95.1% to 98.2% for SARS-CoV-2, 88.9%–95.2% for influenza A, and 91.7%–100% for influenza B depending on the sample type. The specificity was consistently 100% for all of the targeted viruses. Discussion: The InstaView COVID-19/Flu Ag Combo Test thus demonstrated high performance, ease of use, rapid results, and the ability to precisely detect SARS-CoV-2 and influenza A/B infections, making it an effective tool in streamlining diagnostic workflows, optimizing resource allocation, and improving patient outcomes.